Butterfly Diversity in Harding Park, Patna, Bihar, India: A Case Study of Urban Ecosystem - Ranjan, Alok; Bhardwaj, Manish (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Butterflies serve as crucial bioindicators susceptible to habitat degradation, emphasising the need of green spaces in urban conservation efforts. Current study investigates butterfly diversity in Harding Park, Patna, within a very high density, heavily anthropogenically impacted urban area. This study documented 1,089 butterfly individuals of 45 species belonging to five families using the Pollard Walk Method (100m each) between April and July 2022. The Hesperiidae family was most abundant, comprising 36.2% of total butterfly abundance, with Rice Swift as highest recorded species followed by Pieridae (27.4%) Nymphalidae (27.6%) and Papilionidae (9%) that were notably prevalent. However, the reduced occurrence of Lycaenidae (8%) indicates a potential need for species specific habitats. Diversity indices (Shannon, Simpson, and Evenness) were mainly used to compare diversity across different months. Shannon diversity peaked in May (3.217), with highest species richness (37 species) and evenness (0.73, whereas the lowest diversity was recorded in July (2.382) and this was associated with an increase in dominance as a few species became predominant during July. In April, the lowest richness (24 species) and abundance (137 individuals) were reported, perhaps attributable to dry, less humid pre-monsoon conditions. Butterfly abundance increased consistently, reaching 540 individuals in July, presumably due to favourable monsoon conditions. The butterfly assemblages of May and June had a similarity of 68%, whereas the July assemblages, with a similarity of approximately 54%, as it distinctly separated from assemblages of other months. The current study highlights the significance of Harding Park in offering green environment and thus microclimatic conditions supporting butterfly populations and other biodiversity. The study further discusses the role of urban parks in conserving biodiversity, particularly in the context of increasing urbanisation.